Multisystem Inflammatory Syndrome in Children (MIS-C) in a Low-income Country: What Treatment Should be Adopted in Case of a Lack of Immunoglobulin? - Abdeladim, Babakhouya; Massilia, Bouhmidi; Aziza, Elouali; Zohair, Elhaddar; Ayad, Ghanam; Maria, Rkain (Reviews on Recent Clinical Trials, 2024)
Introduction: In multisystem inflammatory syndrome (MIS-C), children typically present high-grade fever, gastrointestinal symptoms, Kawasaki-like symptoms, and even a toxic shock-like syndrome days to weeks after recovering from SARS-CoV-2 infection. It is important to raise awareness of this condition in order to have early diagnosis and immediate treatment of patients. We have, herein, reported 44 cases of MIS-C with various risk factors and symptoms. Furthermore, we have emphasized the efficacy of experience in treating children with MIS-C with high-dose corticosteroids as an alternative to immunoglobulin in low-income countries. Methods: We conducted a targeted survey of MIS-C from early May 2020 to October 2022 on 44 children and adolescents with characteristics of multisystem inflammatory syndrome admitted to the pediatric department of the university hospital center in Oujda, Morocco, to which patients diagnosed with MIS-C were referred. The case definition included six criteria: serious illness leading to hospitalization, age under 18 years, fever of at least 24 hours, laboratory evidence of inflammation, multi-organ involvement, biological inflammatory syndrome, and evidence of coronavirus infection based on polymerase chain reaction, antibody testing or exposure to people with COVID-19 in the past month. The criteria used to diagnose myocarditis were impaired left ventricular function, central mitral leak, and elevation of BNP or pro-BNP. Coronary involvement was assessed by the z-score and the criteria for its presence was a z-score equal to or greater than 2.5. Results: Our study included 44 children and adolescents with MIS-C in our hospital, with male predominance (79%) and a median age of six years. Cardiovascular involvement was present in 91%, mucocutaneous in 78%, gastrointestinal in 70%, hematologic in 84%, and respiratory in 2% of patients. Coronary abnormalities (z-score ≥ 2.5) were documented in 21 cases (48%). Glucocorticoids were frequently used in comparison to immunoglobulin, which were uncommonly available and expensive. Conclusion: The therapeutic protocol that was adopted was high doses of short-term prednisone (Cortancyl) at 4mg/kg/day for 4 days. Favorable outcome was noted in all patients over a 2-year period.
Keywords: prednisone